Gender Differences in Relationship Between Self-Esteem and Achievement Motivation in Primary School Students - Utami, Karinta; Muliasari, Ema Astri; Fitria Firizki, Cicin Solihat; Surastri, Nuryanti; Hidayat, Syarip; Babu, Sameer (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2022)
The purpose of this study is to analyze about the association between self-esteem and achievement goals in various student gender’s groups. This study employed a descriptive method with a quantitative approach. The participants in this study were 260 fifth grade students in Tasikmalaya, Indonesia. The research instrument utilized a questionnaire adapted from Rosenberg self-esteem questionnaires and achievement motivation questionnaires adapted from Mc Clelland theory. Data analysis of this study used SPSS Pearson correlation and t-test. The findings revealed that there is a significant differen t level for various groups of gender-esteem and achievement motivation with a number of significancy was 0.21(higher than 0.05). Meanwhile, for fifth-grade students, there is a significant differen t level for various groups of gender-esteem and achievement motivation. This research is beneficial to the advancement of knowledge, particularly in the fields of psychology and primary education.